Fenomena Fear of Missing Out (FOMO) dalam Keputusan Investasi Saham Syariah di Kalangan Mahasiswa STAI Ibnu Rusyd - Ratna Himawati; Tria Mei Diana (ProBisnis : Jurnal Manajemen, 2026)
Fenomena The fear of missing out (FOMO) phenomenon has become increasingly prevalent among university students, particularly in sharia stock investment activities. FOMO tends to lead individuals to make rapid and less-considered investment decisions due to concerns about missing out on trending profit opportunities. This study aims to examine the impact of FOMO on students’ decision-making in sharia stock investments. A quantitative approach was employed, with data collected through questionnaires distributed to students involved in sharia stock investing. The results reveal that FOMO significantly influences investment behavior, with students more likely to follow market trends rather than conduct thorough analysis. This situation may heighten investment risks and potentially conflict with the prudential principles of sharia investing. Therefore, enhancing financial literacy and strengthening understanding of sharia investment principles are crucial to support more rational and well-informed decision-making among students. This research uses a quantitative approach with questionnaires distributed to 100 students who actively invest in sharia stocks. The results show that FOMO has a positive and significant effect on sharia stock investment decisions. Sharia financial literacy weakens the effect of FOMO, while social media intensity strengthens it. The main implication of This this study is the need to strengthen sharia financial literacy and value-based investment education among students to avoid speculative investment behavior and ensure compliance with sharia principles.